How do you derive this equation: y = sin ^ 3 (cosx^3)
Follow Math Help Forum on Facebook and Google+
This is the chain rule if the cosine is inside the sine, which what this seems to be.
Originally Posted by mathamatics112 How do you derive this equation: y = sin ^ 3 (cosx^3) You need to use the chain rule several times: And so on. Can you continue?
y= sin^3( cos x^3) = 3 sin ^ 2 ( cos x^3)(coz(cosx^3))(-sinx^3)(3x^2) = 9 x^2(sin^2)(cos(cos x^3))(-sin x^3)) are my steps right?
Originally Posted by mathamatics112 y= sin^3( cos x^3) = 3 sin ^ 2 ( cos x^3)(coz(cosx^3))(-sinx^3)(3x^2) = 9 x^2(sin^2)(cos(cos x^3))(-sin x^3)) Aren't you missing something in that last line?
i'm not seeing it
Originally Posted by mathamatics112 i'm not seeing it Did you look at the part that I highlighted? You have sitting by itself. You are taking the sine-squared of what?
View Tag Cloud